Technical Efficiency-Food Security Nexus in Kaduna State, Nigeria: A Case Study of Poultry Egg Farmers - Oyakhilomen, Oyinbo (Consilience, 2015)
This study analysed the technical efficiency of poultry egg production for sustainable food security in the study area using primary data. The data were analysed using stochastic frontier, the US Department of Agriculture (USDA) food security measurement, and correlation analysis to determine the relationship between technical efficiency and food security. The result of the study revealed that the poultry egg farmers had a very low technical efficiency of 23%, which implies that the poultry egg farmers have a chance of improving their technical efficiency by 77% using their available resource efficiently. The result also revealed that few of the households (10%) were food secure while most of them (90%) were food insecure at different levels of food insecurity. The result of the study further indicated a direct relationship between technical efficiency and food security at 1% level of probability, implying that as average productivity increases, food security increases. The policy implication is that food security among the poultry egg farmers is linked with improving their farm efficiency. If food security is to be ensured among the poultry egg farmers, their farming activities must be efficient. The study recommended that the poor food security status of the poultry egg farmers be improved by addressing their low level of technical efficiency through ensuring the efficient utilization of their available resources. This calls for emphasis on extension activities to focus on training poultry egg farmers on improved production management practices.